2016
DOI: 10.1016/j.jshs.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Single dose of intra-muscular platelet rich plasma reverses the increase in plasma iron levels in exercise-induced muscle damage: A pilot study

Abstract: BackgroundPlatelet rich plasma (PRP) therapy is widely used in enhancing the recovery of skeletal muscle from injury. However, the impact of intramuscular delivery of PRP on hematologic and biochemical responses has not been fully elucidated in exercise-induced muscle damage. The purpose of this investigation the effects of intramuscular delivery of PRP on hematologic and biochemical responses and recovery strategy muscle damage induced by high intensity muscle exercise (exercise-induced muscle damage, EIMD).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…In similar studies done by Young et al, (1998) and Awad et al, (2000) who had seeded stem cells in collagen hydrogel for treatment of tendinitis found that the cells reoriented and expanded significantly with time. Bashandy et al, (2014) and Punduk et al, (2014) noticed a significant elevated activity of serum Alkaline Phosphatase and Creatinine kinase in most of the common musculoskeletal affections and post exercise in horses. An apparent decrease in serum Creatinine kinase level in Autologous Platelet Rich Plasma and collagen hydrogel group was noticed due to the sustained action of Autologous Platelet Rich Plasma in the collagen scaffold environment (Harrison et al, 2011 andPunduk et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In similar studies done by Young et al, (1998) and Awad et al, (2000) who had seeded stem cells in collagen hydrogel for treatment of tendinitis found that the cells reoriented and expanded significantly with time. Bashandy et al, (2014) and Punduk et al, (2014) noticed a significant elevated activity of serum Alkaline Phosphatase and Creatinine kinase in most of the common musculoskeletal affections and post exercise in horses. An apparent decrease in serum Creatinine kinase level in Autologous Platelet Rich Plasma and collagen hydrogel group was noticed due to the sustained action of Autologous Platelet Rich Plasma in the collagen scaffold environment (Harrison et al, 2011 andPunduk et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Bashandy et al, (2014) and Punduk et al, (2014) noticed a significant elevated activity of serum Alkaline Phosphatase and Creatinine kinase in most of the common musculoskeletal affections and post exercise in horses. An apparent decrease in serum Creatinine kinase level in Autologous Platelet Rich Plasma and collagen hydrogel group was noticed due to the sustained action of Autologous Platelet Rich Plasma in the collagen scaffold environment (Harrison et al, 2011 andPunduk et al, 2014). MMP13 levels were assessed to evaluate the extent of extracellular matrix damage (Clegg et al, 2007 andRiley et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Similar changes in iron levels were observed by Punduk et al in volunteers who received intensive platelet-rich plasma therapy during intense exercise. This therapy aimed to improve muscle regeneration, which was damaged by the use of high-intensity exercises (exercise-induced muscle damage, EIMD) [26]. It can be assumed that the ability to chelate iron ions, through the active compounds contained in chokeberry, can also counteract damage to muscle bres.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies described positive results after injection of PRP in patients with injured skeletal muscles, and no negative side effects were reported [311,312] (Table 9). Contrasting results were obtained when PRP was compared to saline [313][314][315].…”
Section: Muscle Injuriesmentioning
confidence: 99%